Rekayasa Growth Light LED Berbasis Solar Cell untuk Percepatan Pertumbuhan Tanaman Hidroponik Pada Usaha “Sidomulyo Hidroponik” - Rafil Arizona; Jhonni Rahman; Syarifah Farradina; Zaflis Zaim; Prima Titisari (Universitas Lancang Kuning, 2022)
This activity is a research-based community service program. The goal of this community service program is to create a series of solar cell-based grow light led lights as a source of electrical energy in the